Transport of Atrazine and Dicamba through Silt and Loam Soils - James Tindall; Michael Friedel (Global Journal of Earth Science and Engineering, 2016)
The objectives of this research were to determine the role of preferential flow paths in the transport of atrazine (2-chloro-4-(ethylamino)-6-(isopropylamino)-s-triazine) and dicamba (3-6-dichloro-2-methoxybenzoic acid) through silt and loam soils overlying the High Plains aquifer in Nebraska. In a previous study, 3 of 6 study areas demonstrated high percentages of macropores; those three areas were used in this study for analysis of chemical transport. As a subsequent part of the study, 12 intact soil cores (30-cm diameter by 40-cm height), were excavated sequentially, two from each of the following depths: 0-40cm and 40-80cm. These cores were used to study preferential flow characteristics using dye staining and to determine hydraulic properties. Two undisturbed experimental field plots, each with a 3-m2 surface area, were installed in three study areas in Nebraska. Each was instrumented with suction lysimeters and tensiometers at depths of 10cm to 80cm in 10-cm increments. Additionally, each plot was planted with corn (Zea mays). A neutron probe access tube was installed in each plot to determine soil water content at 15-cm intervals. All plots were enclosed with a raised frame (of 8-cm height) to prevent surface runoff. All suction lysimeters were purged monthly for three months and were sampled immediately prior to pre-plant herbicide application to obtain background chemical concentrations. Atrazine and dicamba moved rapidly through the soil, but only after a heavy rainfall event, probably owing to the presence of preferential flow paths and lack of microbial degradation in these soil areas. Staining of laboratory cores showed a positive correlation between the percent area stained by depth and the subsequent breakthrough of Br- in the laboratory and leaching of field-applied herbicides owing to large rainfall events. Suction lysimeter samples in the field showed increases in concentrations of herbicides at depths where laboratory data indicated greater percentages of what appeared to be preferential flow paths. Concentrations of atrazine and dicamba exceeding 0.30 and 0.05µg m1-1 were observed at depths of 10-30cm and 50-70cm after two months following heavy rainfall events. It appears from the laboratory experiment that preferential flow paths were a significant factor in transport of atrazine and dicamba. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the U.S. Government or GNS.